A meta-analytic review of the approach-avoidance achievement goals and performance relationships in the sport psychology literature - Marc Lochbaum; Jarrett Gottardy (Elsevier, 2015)
Purpose: To summarize the approach-avoidance achievement goal and performance in the sport psychology literature. Methods: A total of 17 published studies, two of which provided two samples, were located. Accepted meta-analytic procedures were used with Hedges g as the effect size metric. From the 17 studies, 73 effect sizes were calculated. Results: Results based on a random effects model indicated that the performance goal contrast had the largest facilitative impact on performance followed by the mastery and performance approach goals. Both of the avoidance goals performance and mastery had small non-significant and detrimental effects on performance. The homogeneity statistics revealed significant heterogeneity for the approach and avoidance performance goals. Categorical moderator variables were examined for study sex composition (male, female, or mixed), mean age of sample (<18 years or ≥18 years), study setting (lab or naturalistic), and nature of performance variable (objective or subjective). Conclusion: The performance goal contrast holds value for sport performance research. Contrary to approach-avoidance predictions, the mastery-approach goal and performance effect size was significant and of equal magnitude as the performance approach goal and performance effect size. Thus, future research should closely test the efficacy of both the mastery- and performance contrasts in impacting performance of sport tasks. Last, the significant effect sizes reported in this review are in stark contrast to contemporary meta-analytic findings in education. Differences in the approach-avoidance goals in sport and education relative to performance should be researched further.